Postdecision Evidence Integration and Depressive Symptoms - Moses-Payne, Madeleine E.; Rollwage, Max; Fleming, Stephen M.; Roiser, Jonathan P. (Frontiers in Psychiatry, 2019)
Background: Metacognition or the ability to reflect on one’s own thoughts may be important in the development of depressive symptoms. Recently, Rouault and colleagues (2018a) reported that depressive symptoms were associated with lower metacognitive bias (overall confidence) during perceptual decision-making and a trend towards a positive association with metacognitive sensitivity (the ability to discriminate correct and incorrect decisions). Here, we extended this work, investigating whether confidence judgements are more malleable in individuals experiencing depressive symptoms. We hypothesised that depressive symptoms would be associated with greater adjustment of confidence in light of new evidence, presented after a perceptual decision had been made. Methods: Participants (N=416) were recruited via Amazon Mechanical Turk. Metacognitive confidence was assessed through two perceptual decision-making tasks. In both tasks, participants made a decision about which of two squares contained more dots. In the first task, participants rated their confidence immediately following the decision whereas in the second task, participants observed new evidence (always in the same direction as initial evidence) before rating their confidence. Participants also completed questionnaires measuring depressive symptoms and self-esteem. Analysis: Metacognitive bias was calculated as overall mean confidence, while metacognitive sensitivity was calculated using meta-d’ (a response-bias free measure of how closely confidence tracks task performance) in the first task. Post-decision evidence integration was defined as the change in confidence following post-decision evidence on the second task. Results: Participants with more depressive symptoms made greater confidence adjustments (i.e. greater post-decision evidence integration) in light of new evidence (β =.119, p=.045), confirming our main hypothesis. We also observed that lower overall confidence was associated with greater depressive symptoms, though only to a small extent (β =-.099, p=.056), and we did not find an association between metacognitive sensitivity (meta-d’) and depressive symptoms. Notably, self-esteem was robustly associated with overall confidence (β =.203, p<.001), which remained significant when controlling for depressive symptoms. Conclusions: We found that individuals with depressive symptoms were more influenced by post-decisional evidence, adjusting their confidence more in light of new evidence. Individuals with low self-esteem were less confident about their initial decisions. This study should be replicated in a clinically depressed sample.